Ciberperiodismo Móvil: El Peso Específico de La Cuarta Pantalla en El Panorama Informativo Internacional - Parra Valcarce, David (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
We define mobile cyberjournalism as the treatment of the journalistic information that let the sending and the reception of texts, static images (drawings, photographs, infographies...), dynamic images and sounds in an integrated manner, and also the participation of citizens, converted in generators and evaluators of contents, always using the technological capabilities of third generation mobile telephony. It is a market segment in which the journalistic groups around the world are taking position in the beginning of the 21st century. In this particular context, Grupo Planeta, one of the biggest multimedia holdings in Spanish language in Spain and Latin America, is promoting with remarkable strength new projects related to mobile cyberjournalism, facing up to three main challenges: searching a new business model, offering a wide range of services and creating a design adapted to the peculiarities of cellular phone.
Keywords: Cyberjournalism; mobile telephony; 3G; Grupo Planeta